Government-Mandated Discriminatory Policies - Hanming Fang; Peter Norman (The Research Institute of Industrial Economics (IUI), 2001)
This paper provides a simple explanation for why some minority groups are economically successful, despite being subject to government-mandated discriminatory policies. We study an economy with private and public sectors in which workers invest in imperfectly observable skills that are important to the private sector but not to the public sector. A law allows native majority workers to be employed in the public sector with positive probability while excluding the minority from it. We show that even when the public sector offers the highest wage rate, it is still possible that the discriminated group is, on average, economically more successful. The reason is that the preferential policy lowers the majority's incentive to invest in imperfectly observable skills by exacerbating the informational free riding problem in the private sector labor market
Keywords: D31; J45; J71; 330; Discrimination; Informational Free Riding; Income Distribution; Arbeitsmarktdiskriminierung; Diskriminierung; Ethnische Gruppe; Qualifikation; Ökonomischer Anreiz; Öffentlicher Sektor; Privatwirtschaft; Theorie